The Effect of Adolescent Experience on Labor Market Outcomes: The Case of Height - Persico, Nicola; Postlewaite, Andrew; Silverman, Dan (Journal of Political Economy, 2004)
Taller workers receive a wage premium. Net of differences in family background, the disparity is similar in magnitude to the race and gender gaps. We exploit variation in an individual’s height over time to explore how height affects wages. Controlling for teen height essentially eliminates the effect of adult height on wages for white men. The teen height premium is not explained by differences in resources or endowments. The teen height premium is partially mediated through participation in high school sports and clubs. We estimate the monetary benefits of a medical treatment for children that increases height.